Minority gender stress and its effects on mental health as a risk factor for depression in transgender persons: Literature review (Research, Society and Development, 2021)
Transgender people experience disparities in mental health when compared to the general population, studies claim that this behavior may impact the well-being of this population. However, little is known about how multilevel stigma is experienced throughout life and that it can be especially vulnerable to its cumulative effects. Objective: To highlight the effects of minority stress on the life of the transgender population. Method: This is an integrative literature review that followed the PICO strategy to identify factors associated with gender minority stress. The search for the articles was carried out in three electronic databases: Medline, Lilacs and Scielo. The descriptors "Sexual and Gender Minorities", "Transgender People", "Social Stigma", "Mental Health" were used, with complete texts, published in the period from 2011 to 2021, in English, Portuguese and Spanish. Boolean AND operator. Result: 157 articles were found. Thirty-five articles were selected to be read in full and 15 met the criteria of this review. Evidence shows that the transgender population is at higher risk for mental disorders, including anxiety, when compared to heterosexuals. The appearance of signs and symptoms of anxiety are related to the shame and avoidance of this population due to strong discrimination and the lack of social and family support, which causes high levels of distress.